1981
DOI: 10.1515/cclm.1981.19.5.283
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxic Effects of Sera from Patients with Fulminant Hepatitis B on Isolated Rat Hepatocytes in Culture

Abstract: The hepatotoxicity of sera from patients with terminal fulminant hepatic failure has been investigated by cell culture techniques. It could be shown that both untreated and heat-treated sera are cytotoxic in nature. Compared with the action of sera from healthy individuals on liver cells in primary monolayer culture, the pathological sera exhibited significantly different behaviour with respect to morphological and biochemical parameters such as cell adhesion, growth and proliferation, and enzyme release. Hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The importance of using viable functional liver cells in the extracorporeal liver assist devices might also be supported by the results of our recent study, in which intrasplenic transplantation of 10 billion cryopreserved hepatocytes in pigs with the same model of ischemic liver failure delayed the onset of intracranial hypertension, prolonged survival time, lowered blood ammonia and bilirubin levels, and improved blood coagulation (16). We also suggest that treatment in Group 2 pigs was less effective than in Group 2 animals because in the complete hybrid BAL system by placing the charcoal column before the hepatocyte module in the circuit, we protected the cryopreserved normal porcine hepatocytes from the possible toxic effects of hepatic failure plasma (25,26). This could have resulted in improved overall BAL performance.…”
Section: Discussionmentioning
confidence: 93%
“…The importance of using viable functional liver cells in the extracorporeal liver assist devices might also be supported by the results of our recent study, in which intrasplenic transplantation of 10 billion cryopreserved hepatocytes in pigs with the same model of ischemic liver failure delayed the onset of intracranial hypertension, prolonged survival time, lowered blood ammonia and bilirubin levels, and improved blood coagulation (16). We also suggest that treatment in Group 2 pigs was less effective than in Group 2 animals because in the complete hybrid BAL system by placing the charcoal column before the hepatocyte module in the circuit, we protected the cryopreserved normal porcine hepatocytes from the possible toxic effects of hepatic failure plasma (25,26). This could have resulted in improved overall BAL performance.…”
Section: Discussionmentioning
confidence: 93%
“…Plasma from patients with FHF is known to extensively interfere with cellular function. Haas et al (24) demonstrated that the DNA content of rat hepatocytes was decreased in 20% FHF serum. Shi et al (23) demonstrated that FHF serum inhibited the synthesis of protein, RNA, and DNA of Hep G2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies (5,6,25) have demonstrated the inhibitory effects of FHF serum on growth and macromolecular synthesis in hepatocytes. Hughes and coworkers investigated the cytotoxicity of plasma from patients with various types of liver diseases using a microtoxicity assay system.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Haas et al. demonstrated that the DNA content of rat hepatocytes was decreased in 20% FHF serum ( 25). By using rapidly growing Hep G2 cells for our experiments, we have increased the sensitivity for detecting this type of interaction with liver cells compared with the experiments previously conducted in nonproliferating primary cultures of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%